The Impact of Macroeconomic Variables on Third-Party Funds in Islamic Banks - Surya Saputra; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study is motivated by the increasing role of Islamic banking in the national financial system and the inconsistent findings of previous studies regarding the determinants of Third-Party Funds (DPK). This study aims to analyze the effect of Gross Domestic Product (GDP), inflation, the BI Rate, and the exchange rate on the amount of Third-Party Funds in Islamic Commercial Banks during the 2016–2024 period. The Covid-19 pandemic is also included as a dummy variable to capture changes in public saving behavior during the crisis period. This study employs a quantitative approach using quarterly time-series secondary data. The data were analyzed using multiple linear regression with the Newey-West estimator through Stata 17 to address autocorrelation problems. The results indicate that GDP, inflation, and the exchange rate have a positive and significant effect on Third-Party Funds, while the BI Rate has a negative and significant effect. Simultaneously, all variables significantly influence Third-Party Funds in Islamic Commercial Banks. These findings imply that macroeconomic stability plays an important role in strengthening fund collection in Islamic banking.